Statistics anxiety, basic mathematics skills and academic performance among undergraduate psychology students - Abd Hamid, Harris Shah; Sulaiman, Muhamad Karimi (2014)
Statistics anxiety is a perennial problem among social science students who are faced with statistics as a programme requirement. At one Department of Psychology in Malaysia, the failure rates for a statistics course, across six semesters spanning 2010 to 2013, were the highest compared to other undergraduate courses. Thus, this study attempts to investigate the relationship between statistics anxiety, basic mathematics skills and academic performance among undergraduate psychology students. A survey that included an adapted Statistics Anxiety Scale (SAS) and basic mathematic skills were distributed to the students at the beginning of the semester. Academic performance was measured through mid-semester examination and three quizzes. Scores from 80 students was analysed by linear regression analysis. The adapted SAS had adequate reliability, Cronbach alpha = .946. It was found that both mathematics skills scores and statistics anxiety scores are significant predictors of the overall academic performance. The resulting regression equation was significant, F(2,77)=14.255, p<.001, R2=.270. The results of the study confirmed that academic performance was negatively correlated with statistics anxiety and positively correlated with basic mathematics scores. The SAS can be used for assessing students’ anxiety as part of class intervention, but its factor structure needs further investigation.